2021
DOI: 10.1111/cen.14437
|View full text |Cite
|
Sign up to set email alerts
|

Growth and relationship of phenotypic characteristics with gonadal pathology and tumour risk in patients with 45, X/46, XY mosaicism

Abstract: Sex development is controlled genetically. Disorders of sex development (DSD) are caused by sex chromosome abnormalities or pathogenic variants in certain genes impairing the sex differentiation. In the aetiology of DSD, the mosaicism of 45, X and 46, XY or variants, often called 'mixed gonadal dysgenesis' (MGD), plays an important role and is seen with an incidence of one in 15,000 live births. 1,2 The mosaicism occurs due to the loss of Y chromosome in male embryos in post-zygotic mitotic divisions. The timi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The preoperative diagnosis of this disease should be combined with clinical and laboratory endocrine and sex hormone levels, imaging examination, chromosome karyotype and other tests. (11,12); the final diagnosis is based on pathological results. Also, The differential diagnosis is mainly differentiated from other diseases with abnormal gonadal development.…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative diagnosis of this disease should be combined with clinical and laboratory endocrine and sex hormone levels, imaging examination, chromosome karyotype and other tests. (11,12); the final diagnosis is based on pathological results. Also, The differential diagnosis is mainly differentiated from other diseases with abnormal gonadal development.…”
Section: Discussionmentioning
confidence: 99%
“…The broad range of phenotypical variations in MGD may be explained by the proportion of mosaic karyotype that is expressed in gonadal and other tissue cells [ 14 , 15 ]. Frequently Turner syndrome characteristics are found in individuals with 45,X/46,XY, the presence of 45,X cell line is associated with Turner syndrome fenotype [ 5 , 7 , 15 , 16 ]. Gonadal development and differentiation is determined by the predominant karyotype in gonadal tissue cells.…”
Section: Discussionmentioning
confidence: 99%
“…For streak-like gonads this should be done even if they seem morphologically not involved [ 6 ]. In mosaic 45,X/46,XY patients reared as males with scrotal testis, the risk for germ cell neoplasia is very low, but some cases are reported, therefore, regular examination after biopsy should be included in follow-up protocols [ 16 ]. Orchidopexy with biopsy of testicular part and resection of atypical, usually triangular, dysgenetic testicular outgrowth is advocated.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-eight patients were scored for external genital virilization according to the EMS. The results showed that the EMS of patients raised as females was 1 (0-3) [median (range)] and that of the males was 7.63 (3)(4)(5)(6)(7)(8)(9)(10)(11) [median (range)] (P = 0.0001 < 0.001) (Table 1).…”
Section: External Genitalia Phenotypementioning
confidence: 99%
“…These patients were divided into a male phenotype group (20 cases) and a female phenotype group (18 cases) according to their external genital phenotype. The EMS of patients raised as female was 1 (0-3) [median (range)], and that of males was 7.63 (3)(4)(5)(6)(7)(8)(9)(10)(11) [median (range)]. EMS < 3 points indicates a female phenotype, and EMS > 3 points indicates a male phenotype.…”
Section: Correlation Analysismentioning
confidence: 99%